2017
DOI: 10.1111/1751-7915.12883
|View full text |Cite
|
Sign up to set email alerts
|

Development of a specific fluorescent phage endolysin for in situ detection of Clostridium species associated with cheese spoilage

Abstract: SummaryLate blowing defect (LBD) is a major cause of spoilage in cheeses, caused by the growth of Clostridium spp. in the cheese matrix. We investigated the application of CTP1L, a bacteriophage endolysin active against Clostridium tyrobutyricum, and its enzymatically active and cell wall‐binding domains (EAD and CBD) attached to green fluorescent protein (GFP) to detect dairy‐related Clostridium species by fluorescence microscopy. GFP‐CTP1L and GFP‐CBD demonstrated specificity for Clostridium spp. by labellin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 54 publications
2
12
0
Order By: Relevance
“…As mentioned for tuberculosis, even though there are PCR-based assays faster than the standard method, they cannot differentiate among live and dead cells, which is critical for relevant results, and it is solved with this assay. 43) Similar techniques have been also reported for the detection of Salmonella, 44,45) E. coli, 46) and Clostridium 47,48) in different types of samples.…”
Section: Detection Of Pathogens In Clinical Settings and Food Industrysupporting
confidence: 56%
“…As mentioned for tuberculosis, even though there are PCR-based assays faster than the standard method, they cannot differentiate among live and dead cells, which is critical for relevant results, and it is solved with this assay. 43) Similar techniques have been also reported for the detection of Salmonella, 44,45) E. coli, 46) and Clostridium 47,48) in different types of samples.…”
Section: Detection Of Pathogens In Clinical Settings and Food Industrysupporting
confidence: 56%
“…The natural ability of phages to infect (and kill) a certain bacterial host range has led to their exploitation over the past decades for the development of diagnostic tools and antibacterials for use in medicine [ 25 , 26 ], food production [ 27 , 28 , 29 , 30 , 31 ], and biotechnology [ 32 , 33 , 34 ]. For example, phages can be used to treat Campylobacter [ 35 ] or Salmonella [ 27 ] infections of chicken flocks, or added to feed to kill Clostridium and intestinal coliforms in pigs [ 36 ]; added to ready-to-eat foods to prevent Salmonella [ 37 ] or Listeria [ 38 ] contaminations; or mixed with various food products to act as bio-preservatives [ 39 , 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, the localization of LysPBC2 on the developing spores may be evolutionarily beneficial to both phage and host if the endolysin promotes spore germination under favorable environmental conditions. Recently, one study revealed that a Clostridium tyrobutyricum phage endolysin, CTP1L, can bind to clostridial spores (40). Although they did not find an SBD within CTP1L, it is intriguing to identify additional SBDs from phages infecting spore-forming bacteria.…”
Section: Discussionmentioning
confidence: 99%